Collective action to secure property rights for the poor: A case study in Jambi Province, Indonesia - Komarudin, Heru; Siagian, Y.; Colfer, C.J.P. (International Food Policy Research Institute, 2008)
This study presents an approach to analyzing decentralized forestry and natural resource management and land property rights issues, and catalyzing collective action among villages and district governments. It focuses on understanding the current policies governing local people’s access to property rights and decision making processes, and learning how collective action among community groups and interaction among stakeholders can enhance local people’s rights over lands, resources, and policy processes for development. The authors applied participatory action research in two villages, one each in the Bungo and Tanjabbar districts of Jambi province (Sumatra), Indonesia, to facilitate identification of priorities through phases of planning, action, monitoring, and reflecting. This study finds that action research may be an effective strategy for fostering collective action and maintaining the learning process that leads groups to be more organized and cohesive, and district government officials to be more receptive to stakeholders. A higher level of collective action and support may be needed to avoid elite capture more effectively.